Building your library career with Web 2.0 - Gross, Julia (Chandos information professional series., 2011)
Many professionals in the Library and Information Services (LIS) area are using Web 2.0 to deliver content and reaching out to connect with library users. This book applies these technologies to help shape your own career development plan. Increased online connectivity has opened up new opportunities for professionals to network, learn and grow in their careers; in an online world, where many of us have a digital footprint already, new rules apply. This readable guide builds on the solid foundation of previous library career books. The social networking tools described will supplement the trad.